2018
DOI: 10.1002/jmri.26313
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Evaluation of an R2* Method for Assessing Liver Iron Concentration (LIC) Against FerriScan: Derivation of the Calibration Curve and Characterization of the Nature and Source of Uncertainty in the Relationship

Abstract: Background FerriScan is the method‐of‐choice for noninvasive liver iron concentration (LIC) quantification. However, it has a number of drawbacks including cost and expediency. Purpose/Hypothesis To characterize an R2*‐based MRI technique that may potentially be used as an alternative to FerriScan. This was accomplished through the derivation of a calibration curve that characterized the relationship between FerriScan‐derived LIC and R2*. The nature and source of uncertainty in this curve were investigated. It… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 22 publications
2
30
0
Order By: Relevance
“…Several large studies comparing liver iron concentration (LIC) by R2* and by Ferriscan ® R2 have identified substantial bias between R2* and R2 LIC estimates. [4][5][6] We postulated that the original Ferriscan R2 calibration overestimates LIC at high iron concentrations, exaggerating disagreements between the two techniques.…”
Section: Fixing the Mri R2-iron Calibration In Livermentioning
confidence: 99%
See 1 more Smart Citation
“…Several large studies comparing liver iron concentration (LIC) by R2* and by Ferriscan ® R2 have identified substantial bias between R2* and R2 LIC estimates. [4][5][6] We postulated that the original Ferriscan R2 calibration overestimates LIC at high iron concentrations, exaggerating disagreements between the two techniques.…”
Section: Fixing the Mri R2-iron Calibration In Livermentioning
confidence: 99%
“…The calibration error is sufficient to completely explain the differences between LIC by R2* and Ferriscan ® R2 described in previously studies. [4][5][6] Importantly, any attempts to "calibrate" R2* or other MRI methods against Ferriscan ® need to account for this bias.…”
Section: Fixing the Mri R2-iron Calibration In Livermentioning
confidence: 99%
“…The second relates to the intrinsic limitations of MRI techniques for measurement of liver iron content. In addition to the importance of the skill of the radiologic team (both technician and radiologist) for the quality of the examinations, each technique has its own limitation: R2 relaxometry requires regular calibration of the apparatus by phantoms, is prone to respiratory motion artefacts and is influenced by steatosis; R2* is influenced both by iron and fat (explaining the development of multipeak spectral modelling methods) and its calibration is also controversial; and SIR requires a careful reproduction of Rennes University technical modalities and exhibits a loss of linearity at LIC values > 350 µmol/g (a situation rarely seen in haemodialysis-associated haemosiderosis) [15,19,[46][47][48]. Lastly, the variability of hepatic concentration in some liver diseases can also influence MRI measurement [42].…”
Section: Discussionmentioning
confidence: 99%
“…Compared to traditional MRI imaging based on T 1 ‐ or T 2 ‐weighted signal intensity, MRI relaxometry is more robust for quantitative comparison as it is less sensitive to nuisance parameters such as coil positioning or scanner variabilities . Among other applications, relaxometry has been used to detect brain abnormalities and myocardial fibrosis or evaluate metabolic imaging, liver iron content (LIC), and contrast agent (CA) properties …”
Section: Introductionmentioning
confidence: 99%
“…This amounts to assuming that relaxometry data are lognormally distributed, rather than normally distributed. In fact, the log transform has been used occasionally for both linear mixed models and LIC calibration curves . Recently, the gamma distribution has also been used to account for the constant CV in neuroimaging relaxometry data .…”
Section: Introductionmentioning
confidence: 99%